The development of Chemistry Teaching Guide (CTG) on electrolyte solution and redox reaction based on scientific inquiry. Issue 1 (January 2021) - Solikhin, F; Sari, L P
Abstract: The purpose of this study is to develop a chemistry teaching guide (CTG) for electrolyte solution and redox reaction based on scientific inquiry and find out its quality through the assessment of high school chemistry teachers. The choice of electrolyte solution and redox reaction material because this material is material that is easily developed into a scientific inquiry-based activity. This is research and development (R&D). The CTG was assessed by high school chemistry teachers who had taught the material for at least 2 years. The quality of the results of development is reviewed from the 5 assessment components, namely content, presentation, language, implementation, and display. The results of this study are that CTG based on scientific inquiry has been developed. The quality of the CTG is Very Good in terms of the results of the chemistry teachers assessment. Thus, CTG is feasible to be used by teachers as a guide in learning electrolyte solution and redox reactions based on scientific inquiry.